Visible pedagogic work: parenting, private tutoring and educational advantage in Australia. Issue 3 (3rd May 2016) - Sriprakash, Arathi; Proctor, Helen; Hu, Betty
Abstract : This article explores parents' use of private tutoring services for their primary school children in Sydney, Australia's largest city. Using Bernstein's theories of invisible and visible pedagogies, we look, through the eyes of a small group of middle-class Chinese-background interviewees, at the tensions between certain pedagogic forms associated with private tutoring and schooling in contemporary contexts of educational competition. We show how some parents are openly seeking more explicit, visible forms of instruction through using private tutoring, to compensate for the perceived 'invisible', pedagogically progressive approach of Australian primary schooling. We argue that these parents' enlistment of supplementary tutoring is a considered approach to their identification of a mismatch between (apparently) relaxed, child-centred classroom practices, and the demands of the more traditional examinations that regulate entry points to desired educational sites such as academically selective high schools and prestigious universities. Our findings show how paid tutoring is a contemporary pedagogic strategy for securing educational advantage, not just a 'cultural' practice prevalent among certain migrant communities, as it is often characterised. We suggest that an analytic focus on pedagogy can help connect issues of class, culture and competition in research on home–school relationships, offering a productive way for the field to respond to the tensions these issues engender.